2015
DOI: 10.1371/journal.pone.0118341
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl-Terminal Truncations Alter the Activity of the Human α-Galactosidase A

Abstract: Fabry disease is an X-linked inborn error of glycolipid metabolism caused by deficiency of the human lysosomal enzyme, α-galactosidase A (αGal), leading to strokes, myocardial infarctions, and terminal renal failure, often leading to death in the fourth or fifth decade of life. The enzyme is responsible for the hydrolysis of terminal α-galactoside linkages in various glycolipids. Enzyme replacement therapy (ERT) has been approved for the treatment of Fabry disease, but adverse reactions, including immune react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 110 publications
0
5
1
Order By: Relevance
“…Other approaches for improving the intrinsic limitations of GLA include rational mutagenesis of cysteine residues 49 , active site, dimer interface, and glycosylation sites 50 , deletion of C-terminal sequences 51 , rational modification of alternative enzymes 32 , the use of alternative expression hosts, such as moss 52 and tobacco cells 48 , glycoengineering to improve affinity to the M6P receptor or increase M6P moieties on the enzyme 32,[53][54][55] , and fusion proteins for improved tissue targeting 56,57 . While each of these approaches addresses aspects of intrinsic GLA shortcomings, our approach allows for the comprehensive optimization of multiple properties simultaneously via high-throughput screening of variant libraries under conditions that mimic the path the therapy is exposed to and the natural inactivation strategies it may encounter in the human body upon administration as ERT.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches for improving the intrinsic limitations of GLA include rational mutagenesis of cysteine residues 49 , active site, dimer interface, and glycosylation sites 50 , deletion of C-terminal sequences 51 , rational modification of alternative enzymes 32 , the use of alternative expression hosts, such as moss 52 and tobacco cells 48 , glycoengineering to improve affinity to the M6P receptor or increase M6P moieties on the enzyme 32,[53][54][55] , and fusion proteins for improved tissue targeting 56,57 . While each of these approaches addresses aspects of intrinsic GLA shortcomings, our approach allows for the comprehensive optimization of multiple properties simultaneously via high-throughput screening of variant libraries under conditions that mimic the path the therapy is exposed to and the natural inactivation strategies it may encounter in the human body upon administration as ERT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Qui et al showed that mutants C90S, C174S, and C90S/C174S are enzymatically active, structurally intact, and thermodynamically stable, as measured by circular dichroism and thermal denaturation [ 37 ]. In another study, C-terminal deletions of the GLA enzyme showed not only better enzymatic performance but also an equal thermal stability at 30 °C, 40 °C, and 50 °C for wild-type and C-terminal GLA mutants [ 46 ]. These studies show that researchers in the field are fully aware of the importance of other parameters than only enzymatic activity to check new putative candidates for ERT in FD.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, this type of mutation is associated with a severe phenotype. However, removal of the first residues has been found to give rise to a protein with superior enzyme activity [ 46 , 47 ].…”
Section: Gla Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of GLA enzyme, was tested in different systems including microbial cell factories such as Escherichia coli and the psychrophilic bacterium Pseudoalteromonas haloplanktis (Ferrer‐Miralles et al, 2011; Rodríguez‐Carmona et al, 2015; U. Unzueta et al, 2015) but since the glycosylation pattern of the protein is very relevant to its final activity, we finally choose to use HEK293F (human embryonic kidney cells) and CHO DG44 cells, widely used in the production of human recombinant proteins. To facilitate the purification of recombinantly produced GLA, a histidine (His) tag (rendering GLA‐His protein) or a cmycHis tag (rendering GLAcmycHis protein) were included in the C‐terminus of the protein, a region of the GLA protein could be modified to increase its enzymatic activity (Meghdari, Gao, Abdullahi, Stokes, & Calhoun, 2015). For the former, GLA‐His was produced in HEK‐293 cells by transfection and transient gene expression while the GLAcmycHis was obtained from CHO cells stably transfected with the GLA coding DNA (Corchero et al, 2011).…”
Section: Nanotechnology‐based Improvements For Ert In Fabry Diseasementioning
confidence: 99%